Nominale Mehrworttermini der russischen Fachsprache - Fan, Yong (Specimina philologiae Slavicae, 1997)
The nominal multi-word terminology (NMT) with a noun as the core element represent a particularly productive language structure, which is familiar in the contemporary terminology of almost all technical communication areas. For this linguistic phenomenon, the "Dictionary of Technology" with 124,000 keywords serves as an illustrative example. Of this, more than 80% of the nominal construction is to be expected.